2018
DOI: 10.1186/s13063-018-2981-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy with MRA fusion image guidance in endovascular iliac artery interventions: study protocol for a randomized controlled trial (3DMR-Iliac-roadmapping study)

Abstract: BackgroundEndovascular iliac artery interventions rely on the use of two-dimensional digital subtraction angiographies with an iodinated contrast agent and ionizing radiation. The amount of iodinated contrast agent should be limited because of its potentially nephrotoxic effects. Three-dimensional (3D) image fusion requires registration of a preprocedural magnetic resonance angiogram (MRA) or computed tomography (CT) angiogram to a perprocedurally acquired cone-beam CT or two fluoroscopic orthogonal projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…nl/; identifier NTR5008; registered on 16 December 2014) was the first prospective, multicenter, randomized trial designed to evaluate whether 3D image fusion during endovascular iliac artery interventions could reduce the amount of administered iodinated CM. The study protocol, which was approved by the Maastricht University Medical Center+ and Maastricht University ethics committee (METC azM/UM), was previously published [70], and all study procedures were conducted in accordance with good clinical practices and applicable laws.…”
Section: Image Fusion In Obstructive Iliac Disease; 3dmr-iliac-roadmamentioning
confidence: 99%
“…nl/; identifier NTR5008; registered on 16 December 2014) was the first prospective, multicenter, randomized trial designed to evaluate whether 3D image fusion during endovascular iliac artery interventions could reduce the amount of administered iodinated CM. The study protocol, which was approved by the Maastricht University Medical Center+ and Maastricht University ethics committee (METC azM/UM), was previously published [70], and all study procedures were conducted in accordance with good clinical practices and applicable laws.…”
Section: Image Fusion In Obstructive Iliac Disease; 3dmr-iliac-roadmamentioning
confidence: 99%
“…Preliminary studies on fusion imaging for lower extremities revascularization was reported in several studies for iliac lesions. [10][11][12] At the moment, fusion imaging is not used routinely for the treatment of femoro-popliteal lesions. Moreover, this technology was described only in hybrid rooms equipped with fixed plane sensors.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues (i.e. reducing fluoroscopy time and the amount of contrast), image fusion of preoperative 3D computed tomography angiogram (CTA) or magnetic resonance angiogram (MRA) with intraoperative fluoroscopy can be utilized [8]- [10]. As noted in [11] this image fusion step can be performed as either 2D-3D registration or 3D-3D registration.…”
Section: Introductionmentioning
confidence: 99%